PACKAGING OF POWDERED PRODUCTS MADE FROM DRIED PUMPKIN (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The article presents a comparative analysis of packaging methods for pumpkin powder. Vacuum packaging, modified atmosphere (MA), metallized polypropylene, polyethylene–foil laminates, and PET containers were tested. The highest efficiency was observed with MA packaging (vitamin C – 93–95%, carotenoids – 95–96%), while polyethylene–foil was considered cost-effective. Vacuum packaging preserved high biological value but showed agglomeration. Metallized polypropylene was recommended as a low-cost option, whereas PET containers accelerated vitamin and pigment loss due to light exposure.